Penerapan Problem Based Learning untuk Meningkatkan Aktivitas dan Hasil Belajar Biologi Siswa SMA - Maria Naya Waani; Rudi A. Repi; Ferny M. Tumbel (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This classroom action research evaluates the effectiveness of Problem Based Learning in learning Biology on the topic of environmental change at Rosa de Lima Catholic High School Tondano, with the aim of improving the activities and learning outcomes of grade X students. The method used is two action cycles with stages of planning, implementation, observation, and reflection. The subjects are 10 students. Tools include Teaching Modules and Student Worksheets; Data was collected through observation sheets of teacher and student activities (scales 1–4) and 10-item learning outcome tests each cycle. The descriptive analysis calculates the grade average and classical completeness against the Minimum Completeness Criterion of 75. The results showed consistent improvement from cycle I to cycle II. Classical completeness increased from 66% (6 out of 9 students attended; average 76.67) to 90% (9 out of 10 students; average 81.00). The teacher's activity observation score increased from 3.75 to 3.91, while the student's activity from 3.50 to 3.60. The increase is fueled by the formulation of contextual problems, facilitation of guiding questions, individualized feedback, and more disciplined time management, which strengthens engagement, collaboration, and scientific reasoning. The findings indicate that Problem Based Learning is effective in improving Biology learning activities and outcomes on the topic of environmental change. This study adds to the empirical evidence in the context of high schools with low initial completeness and suggests further exploration of other Biology topics along with measurements of critical thinking skills and scientific attitudes for a more comprehensive picture of impact.